2019
DOI: 10.2169/internalmedicine.1594-18
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Prognostic Nutritional Index on the Survival of Japanese Patients with Hepatocellular Carcinoma Treated with Sorafenib: A Multicenter Retrospective Study

Abstract: Objective The purpose of this multicenter retrospective study was to investigate the impact of the prognostic nutritional index (PNI) on the survival of Japanese patients with hepatocellular carcinoma (HCC) treated with sorafenib. Methods A total of 178 HCC patients from May 2009 to December 2015 at our affiliated hospitals was included in this study. The PNI was calculated as follows: 10×serum albumin (g/dL)+0.005×total lymphocyte count (per mm 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 40 publications
2
8
0
Order By: Relevance
“…Authors showed that PNI constituted an independent predictor of survival, 21 consistent with the results obtained by the Japanese research group of Hatanaka et al 30 Finally, Hiraoka et al 31 analyzed a cohort of HCC patients treated with lenvatinib and highlighted the strength of PNI in indicating the best nutritional status for introducing treatment with TKI, thus proposing the PNI as an easy-to-use nutritional assessment tool to implement in clinical practice, along with the ALBI score.…”
Section: Discussionsupporting
confidence: 58%
“…Authors showed that PNI constituted an independent predictor of survival, 21 consistent with the results obtained by the Japanese research group of Hatanaka et al 30 Finally, Hiraoka et al 31 analyzed a cohort of HCC patients treated with lenvatinib and highlighted the strength of PNI in indicating the best nutritional status for introducing treatment with TKI, thus proposing the PNI as an easy-to-use nutritional assessment tool to implement in clinical practice, along with the ALBI score.…”
Section: Discussionsupporting
confidence: 58%
“…In the Japanese experience of Hatanaka et al [42], the PNI was a significant factor associated with the duration of Sorafenib therapy and the OS among pre-treatment factors in a cohort of patients treated with Sorafenib. No significant differences in terms of Sorafenib efficacy and serious adverse events rate were found between high-and low-PNI groups.…”
Section: Plos Onementioning
confidence: 89%
“…The participants in a second validation cohort were 76 patients collected in the Innovate STUDY database [42]. Baseline clinical and laboratory characteristics are summarized in Table 3.…”
Section: Plos Onementioning
confidence: 99%
“…It is reported to be a useful tool for assessing the preoperative condition and outcome of patients with gastrointestinal tumors [96]. Some studies have reported that the PNI is a prognostic factor in HCC patients receiving surgical treatment [97,98] or sorafenib treatment [99,100]. The PNI was strongly correlated with the ALBI score and the predictive cut-off values of the PNI for ALBI grade 1 and mALBI grade 2a were 39.0 and 36.0, respectively [101].…”
Section: Nutrition Assessment As a Prognostic Indicatormentioning
confidence: 99%